Plasma membrane-association of SAUL1-type plant U-box armadillo repeat proteins is conserved in land plants - Vogelmann, Katja; Subert, Christa; Danzberger, Nina; Drechsel, Gabriele; Bergler, Johannes; Burmester, Thorsten; Hoth, Stefan (Frontiers in Plant Science, 2014)
Post-translational protein modification plays a pivotal role in the regulation and specific turnover of proteins. One of these important modifications is the ubiquitination of target proteins, which can occur at distinct cellular compartments. At the plasma membrane, ubiquitination regulates the internalization and thus trafficking of membrane proteins such as receptors and channels. The Arabidopsis plant U-box armadillo repeat (PUB-ARM) ubiquitin ligase SAUL1 (SENESCENCE-ASSOCIATED UBIQUITIN LIGASE1) is part of the ubiquitination machinery at the plasma membrane. In contrast to most other PUB-ARM proteins, SAUL1 carries additional C-terminal ARM repeats responsible for plasma membrane-association. Here, we demonstrated that the C-terminal ARM repeat domain is also essential and sufficient to mediate plasma membrane-association of the closest Arabidopis paralog AtPUB43. We investigated targeting of PUB-ARM ubiquitin ligases of different plant species to find out whether plasma membrane-association of SAUL1-type PUB-ARM proteins is conserved. Phylogenetic analysis identified orthologs of SAUL1 in these plant species. Intracellular localization of transiently expressed GFP fusion proteins revealed that indeed plasma membrane-association due to additional C-terminal ARM repeats represents a conserved feature of SAUL1-type proteins. Analyses of transgenic Arabidopsis plants overexpressing N-terminally masked or truncated proteins revealed that interfering with the function of SAUL1-type proteins resulted in severe growth defects. Our results suggest an ancient origin of ubiquitination at the plasma membrane in the evolution of land plants.